Career Maturity for Deaf Children: Obstacles And Solutions - Weni Winarti; Imas Diana Aprilia (Indonesian Journal of Disability Studies, 2021)
This research was conducted at SMK Garut Regency on Deaf children who have difficulties in making decisions about careers at school and post-school careers. The decision to choose student majors is currently based on the strong will of parents, besides that teacher are less able to provide alternatives to the choice of majors they are interested in and are not based on the results of the assessment of talents and interests. Therefore, the purpose of this study is to see the obstacles of students in achieving career maturity based on the results of the needs analysis. This study uses a qualitative approach with descriptive methods. The participants of this study were Deaf children that had an impact on language skills and cognitive abilities in interpreting information, other subjects were classroom teachers, subject teachers, and special education teachers closest to the student's environment. Data collection techniques used observation, interviews, and documentation studies, and data analysis techniques used data triangulation. The results of this study indicate that the obstacles for students in making career decisions are caused by the impact of their deafness so that they are hampered by expressive and receptive communication skills that do not support them to ask questions so that they only get information from outside and find it difficult to interpret the information they get. The encouragement and prestige of parents and friends are other obstacles in determining student decisions that are not following their interests and talents. Another obstacle is that teachers have not specifically assessed the interest in talent for student careers before entering school to date. Based on these findings, a solution to determine the level of career maturity of students at this time requires an assessment of interests and talents which can then be used by teachers or parents in making transition programs in which focus is on developing soft skills for children in terms of making appropriate career decisions.